AC IMPEDANCE ANALYSIS OF CuS-C COMPOSITE SUPERIONIC CONDUCTOR - Safei Purnama; A. K. Jahja (Jurnal Sains Materi Indonesia, 2008)
AC IMPEDANCE ANALYSIS OF CuS-C COMPOSITE SUPERIONIC CONDUCTOR. CuS-C composite superionic conductor has been synthesized by powder metallurgy method. The frequency response of frequency dependent conductivity has been measured by AC complex impedance bridge methods at room temperature, 100 oC and 200 oC. The AC conductivity of superionic materials takes the form σ=σ(0)+Aωn. The carrier hopping rate ωp is obtained from the new expression σ(0)=Aωpn. The conductivity data is analyzed, to obtain the ionic conductivity parameters and hopping rates of CuS-C composite superionic conductor. Arrhenius plot of the conductivity shows a smooth slope change or transition at 323 K or 50 oC and the activation energy for conduction is found to be 0.154 eV. The experimental data for all temperatures shows a clear anomaly at frequencies of 9.0 kHz and higher. For frequencies from 0.1 Hz to up to 9.0 kHz the curve is mainly flat and practically no frequency dispersion at all temperatures is observed. The estimated DC conductivity is 0.5708 Scm-1. The ionic parameters such as prefactorA, exponential power n and hopping frequency ωp are in fact temperature dependent and this is a strong indication that hopping mechanism is the predominant mode of ionic conduction in CuS-C composite.